Effect of Equimolar Sodium Borohydride-Ferric Chloride Concentrations on Nano Zero-Valent Iron/Palm Shell Composites for Simultaneous Nanogold Recovery and Hydrogen Generation - Puteri Nur Syakinah Nordin; Aina Syamimi Noor Helmy; Chan Juinn Chieh Derek; Mohd Fariz Rajuli; Siu Hua Chang (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Gold-containing waste solutions represent both an environmental liability and a valuable secondary resource, yet few existing technologies integrate nanogold recovery with sustainable hydrogen generation from these streams. In this study, the effect of equimolar sodium borohydride–ferric chloride (NaBH₄–FeCl₃) concentrations on the synthesis and performance of nanoscale zero-valent iron (nZVI)/palm shell composites was systematically investigated for the simultaneous recovery of nanogold and generation of hydrogen from gold-containing aqueous solutions. The composites were synthesized at different equimolar NaBH₄–FeCl₃ concentrations (0.5–2.0 M), while maintaining a fixed overall molar ratio, with palm shell biomass employed as a support to suppress particle aggregation and preserve reactive surface area. Nanogold formation was evaluated using UV–Vis spectroscopy via localized surface plasmon resonance, while hydrogen evolution was quantified by a water-displacement method. Surface properties were characterized by BET analysis. Nanogold recovery increased progressively with increasing equimolar precursor concentration, whereas hydrogen production exhibited a non-linear dependence, reaching a maximum of 29.02 mL at 1.5 M, which also corresponded to the highest BET surface area (13.57 m²/g). Further increasing the equimolar NaBH₄–FeCl₃ concentration to 2.0 M led to surface passivation and diminished reactivity. These results demonstrate that equimolar precursor concentration plays a critical role in governing nZVI/palm shell composite structure and functionality. The optimized composite exhibits strong potential as a multifunctional material for integrated precious metal recovery and green hydrogen production, thereby contributing to sustainable circular resource utilization and clean energy technologies. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).